Effect of Xylo-Oligosaccharides (XOS) on Growth Performance, Blood Biochemistry and Total Viable Count in Ileum and Caecum of Broiler Chickens from Day 13-26 - Akter , M.; Akter, N. (International Journal of Poultry Science, 2021)
Objective: This study was undertaken to investigate the effect of xylo-oligosaccharides (XOS) on the growth performance, blood biochemistry and total bacterial count in the intestine of broiler chicken from 13 to 26 days of age. Materials and Methods: A total of 96 day-old Cobb 500 broiler chicks were distributed randomly into four treatment groups with four replicates (6 birds replicate‾1) and fed basal diet (control) from day 1-12. Test diets were formulated with four different levels of XOS (0, 2.5, 5.0 and 7.5 g kg‾1) and offered to the birds from day 13-26. On day 26, the data on growth performance, serum biochemical profile, total viable count in the ileum and cecum, visceral organ weight and carcass yields of the broiler chickens were assessed. Results: There was no effect (p>0.05) of XOS on weight gain and feed intake. However, supplementation of 2.5 g XOS kg‾1 of diet significantly improved the feed conversion ratio (FCR) of the birds. This group of diet also increased (p